2022
DOI: 10.3389/fphar.2022.975800
|View full text |Cite
|
Sign up to set email alerts
|

Potential therapeutic applications of infusions and hydroalcoholic extracts of Romanian glutinous sage (Salvia glutinosa L.)

Abstract: Ethnopharmacological relevance:Salvia glutinosa, also known as the glutinous sage, has been used in Romanian folk medicine in the treatment of inflammation, injuries, and mild infections. However, there is no direct scientific evidence to demonstrate these activities.Aim of the Study: The present research was based on evaluating antioxidant, antiproliferative, and α-glucosidase inhibitory activity of S. glutinosa extracts, as well as the in vivo anti-inflammatory activity.Materials and Methods: Infusions and 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…The antioxidant effects of other Salvia species (e.g., S. blepharochlaena , S. euphratica var. leiocalycina , S. glutinosa , S. transsylvanica , S. syriaca , S. aegyptiaca , S. palaestina , S. absconditiflora , S. cadmica , S. ceratophylla ) are also documented in the literature [ 22 , 28 , 33 , 36 , 49 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antioxidant effects of other Salvia species (e.g., S. blepharochlaena , S. euphratica var. leiocalycina , S. glutinosa , S. transsylvanica , S. syriaca , S. aegyptiaca , S. palaestina , S. absconditiflora , S. cadmica , S. ceratophylla ) are also documented in the literature [ 22 , 28 , 33 , 36 , 49 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mocan et al [ 22 ] showed a modest cytotoxic effect of S. glutinosa and S. transsylvanica against HepG2, A549, and MCF-7 cell lines with IC 50 values greater than 100 μg/mL. Furthermore, Nicolescu et al [ 58 ] evidenced IC 50 values between 131.68 and 293.79 μg/mL for various extracts of S. glutinosa in MCF-7, HepG2, non-small cell lung carcinoma NCI H460, and cervical carcinoma HeLa cells.…”
Section: Resultsmentioning
confidence: 99%
“…Today, various techniques are used for obtaining various sage products [43] and are chosen depending on the desired profile of sage's bioactive compounds in an extract, and the most used techniques have been recently extensively summarized [16]. Currently, the most employed extraction methods (Table 1) are represented by hydrodistillation (HD) [44], steam distillation (SD) [45], ultrasound-assisted extraction (UAE) [46], sonohydrodistillation (SHD) [47], microwave-assisted extraction (MAE) [48] including microwave-assisted hydrodistillation (MHD or MAHD) [49,50], solid-liquid extraction (SLE) [51], Soxhlet extraction (SE) [52], infusion [53], freeze drying (FD) [54,55], solventfree microwave-assisted extraction (SFME) [56], supercritical fluid extraction (SFE) [57], subcritical water extraction (SCWE) [58], and supercritical CO 2 extraction (SC-CO 2 ) [59,60]. The choice of extraction technique was seen to influence phenolic acids and flavonoid composition, where ultrasound-assisted extraction (UAE) gave the highest concentration [61].…”
Section: Extraction Methodsmentioning
confidence: 99%
“…Rowshan et al, (2020) [135] reported a study on the aerial parts of S. multicaulis, which contain high amounts of rosmarinic acid, catechin, vanillin, chlorogenic acid, quercetin, and p-coumaric acid, and possess good antioxidant activity, equal to 8.44 mg/g, as demonstrated by the DPPH scavenging assay, and with a content of phenol of 4.39 mg/g of the dried plant. Nicolescu et al, (2022) [53] reported some interesting results on an unusual species of Salvia, namely S. glutinosa L., the stems and leaves of which were harvested in two different locations in Romania. Two types of extracts, infusion (water extraction with heat) and maceration (hydroalcoholic extraction, room temperature, in the dark), were obtained, characterized qualitatively and quantitatively by LC-DAD-ESI/MS and investigated for their antioxidant properties by means of DPPH, ABTS, and FRAP assays.…”
Section: Antioxidant Activities Of S Officinalis L Spp Individuallymentioning
confidence: 99%
“…There is plenty of evidence of the traditional use of glutinous sage in folk medicine in many countries. In Romania, a decoction of the roots was used against dizziness and an infusion of the flowers and leaves was administered against gastroenteritis and cough pains and to treat injuries and animal bites ( Nicolescu et al., 2022 ). The leaves of S. glutinosa are also used to prepare an infusion for digestion and to treat headaches and sore throats ( Idolo et al., 2010 ) or for culinary purposes as an aromatic herb ( Motti, 2021 ).…”
Section: Introductionmentioning
confidence: 99%